A Software Business Model That Turns Users into Partners. - Clark, Jason P. (Futurist)
Syntiant is working to incorporate philanthropy or, more specifically, “economic self-empowerment,” into the heart of its business model. Empowering people to help themselves via knowledge and a marketplace for knowledge fosters loyalty, stimulates creativity, and creates a potential revenue stream in the process. This approach merges individuals' ideals with their financial interests and shatters the attitude that an organization cannot be philanthropic and make money simultaneously. One of Syntiant's objectives is to facilitate education and social interaction while providing the necessary equipment and connectivity to those who require it most. Syntiant's aim is to introduce a new profit paradigm for a global social media company. The writer, the company's chief technical officer, explains how the concept works.